A Qualitative Exploration of the Personal, Schooling and Structural Factors Contributing to High School Learner Dropout in Philippi - Vushe, Lovemore (Department of Social Development, 2020)
This study, "A qualitative exploration of the personal, schooling and structural factors contributing to high school learner dropout in Philippi” was carried out on a sample of fifteen young people who dropped out of school in Philippi, a township in Cape Town in the Western Cape. Guided by the research questions that sought to explore participants’ own views on the issue, an exploratory qualitative approach was used. A research sample of thirteen females and two males who dropped out of secondary school before completing grade 12 in Philippi was chosen using a snow balling sampling method. The study used a semi-structured interview schedule for face to face interviews with the school dropouts. The findings revealed that learners in Philippi drop out due to a combination of factors personal, schooling and structural. Personal factors like struggling academically, personal negative views on the importance of education, grade repetition shame, teen pregnancy, delinquent behaviour and alcohol and substance abuse contributed to learners’ decisions to quit school before matriculating. School factors included overcrowded classrooms, poorly trained teachers, lack of learning materials and associated poor educational quality, long distances to school and the unsafe learning environments in which some schools were viewed as gang battle grounds also contributed to participants’ decisions to quit school. Structural factors, barriers beyond learners’ control, also contributed to the high learner dropout. These included social, cultural, and economic circumstances. Social factors included lack of social and educational support at home. Participants stated that they dropped out of school because their parents did not encourage and motivate them to complete Matric, did not actively support their academic life and failed to provide the necessary resources and support to ensure they remained focused. Some participants left school in order to respond to cultural issues that needed their attention. Cultural practices like forced marriages, responding to calls to be a traditional healer and behavioral changes emanating from traditional male circumcision created subjective norms and expectations that were not in line with academic progression. Economically, the learners ‘poor financial backgrounds presented an unfair disadvantage in which both absolute and relative poverty strongly influenced their decisions to drop out. Without school uniforms, food and transport fares, some participants opted to drop off in order to look for employment or self sustenance. Recommendations targeted at different stakeholders at different levels to address this early school dropout problem are also discussed. Some recommendations targeted the youths’ attitudes themselves in order to address some personal or individual characteristics, whilst others focused on schools improvement and policies that address existing structural causes. More parental involvement in learners’ educational matters, greater social workers contribution, infrastructure development in poor schools in Philippi, strategic partnerships among civil sector, government departments, parents and schools as well as enhanced teacher support constitute part of the recommendations.